ELECTRON MICROSCOPIC STUDY ON ENLARGED CELLS OF RED SEA BREAM, Pagrus major INFECTED BY THE RED SEA BREAM IRIDOVIRUS (RSIV, GENUS Megalocytivirus, FAMILY Iridoviridae) - Ketut Mahardika (Indonesian Aquaculture Journal, 2009)
Most histopathologycal studies of the red sea bream iridovirus (RSIV) disease in red sea bream have been performed by studying enlarged cells as well as necrotized cells in the spleen and other organs. These enlarged cells have been named as inclusion body bearing cells (IBCs). However, few information is available about detail of ultrastructural features of IBCs produced in the target organs of RSIV-infected fish. In the present study, details of ultrastructural features of IBCs that were produced in the spleen tissue of naturally RSIV-infected red sea bream were investigated under electron microscope. Under electron microscope, RSIV-infected red sea bream had the presence of two types of IBCs: typical IBCs allowing virus assembly within viral assembly site (VAS), and atypical IBCs which degenerate organelles without virus assembly. Other infected-cells were observed as necrotized cells forming intracytoplasmic VAS with large numbers of virions, but without the formation of the distinct inclusion body. Morphogenesis steps on RSIV-infected red sea bream were observed as filamentous-filed virions, partially-filled virions and complete virions with 145-150 nm in size. These findings confirmed that RSIV-infected red sea bream were characterized by formation of typical and atypical IBCs as well as necrotized cells.